Managing future air quality in megacities: A case study for Delhi. (July 2017) - Amann, Markus; Purohit, Pallav; Bhanarkar, Anil D.; Bertok, Imrich; Borken-Kleefeld, Jens; Cofala, Janusz; Heyes, Chris; Kiesewetter, Gregor; Klimont, Zbigniew; Liu, Jun; Majumdar, Dipanjali; Nguyen, Binh; et al.
Abstract: Megacities in Asia rank high in air pollution at the global scale. In many cities, ambient concentrations of fine particulate matter (PM2.5 ) have been exceeding both the WHO interim targets as well as respective national air quality standards. This paper presents a systems analytical perspective on management options that could efficiently improve air quality at the urban scale, having Delhi as a case study. We employ the newly developed GAINS-City policy analysis framework, consisting of a bottom up emission calculation combined with atmospheric chemistry-transport calculation, to derive innovative insights into the current sources of pollution and their impacts on ambient PM2.5, both from emissions of primary PM as well as precursors of secondary inorganic and organic aerosols. We outline the likely future development of these sources, quantify the related ambient PM2.5 concentrations and health impacts, and explore potential policy interventions that could effectively reduce environmental pollution and resulting health impacts in the coming years. The analysis demonstrates that effective improvement of Delhi's air quality requires collaboration with neighboring States and must involve sources that are less relevant in industrialized countries. At the same time, many of the policy interventions will have multiple co-benefits on development targets in Delhi and its neighboring States. Outcomes of this study, as well as the modelling tools used herein, are applicable to other urban areas and fast growing metropolitan zones in the emerging Asian regions. Highlights: Development of GAINS-City policy analysis model for Delhi. Nearly 60 percent of pollution in Delhi caused by PM 2.5 originates from outside. Improvement of Delhi's air quality requires collaboration with neighboring States. Several policy interventions will have multiple co-benefits on development targets.